Visitors’ motivation and perception on Sangiran Early Man Museum, Krikilan Cluster: Motivasi dan persepsi pengunjung terhadap Museum Manusia Purba Sangiran Klaster Krikilan - Theresia L. Oktarisa; Anindia L. Prihatiningtias; Titi S. Prabawa; Linda Susilowati (Berkala Arkeologi, 2021)
One of Indonesia’s tourist destinations which included in the Heritage Tourism category is Sangiran Early Man Site. As a tourist destination, The Sangiran Early Man Museum, Krikilan Cluster and four other museums, needs a concern to some important elements in the development and management of tourism destination. It comprises tourism destination attributes linked to the tourist motivation and perceptions towards necessities compliance, and tourist satisfaction of the destination. Tourist satisfaction became one of indicators whether the tourism destination can be considered as priority tourism destination. This article provides information on visitors’ motivations and perceptions of Krikilan Cluster, the Sangiran Early Man Museum, based on quantitative research conducted on 533 responden. The descriptive results are expected to give contribution towards museum’s maintenance, management, and development to be a primary tourist destination.